On-Site Deployment of an Air-Liquid-Interphase Device to Assess Health Hazard Potency of Airborne Workplace Contaminants: The Case of 3-D Printers - Kim, Boowook; Shin, Jae Hoon; Kim, Hoi Pin; Jo, Mi Seong; Kim, Hee Sang; Lee, Jong Sung; Lee, Hong Ku; Kwon, Hyuk Cheol; Han, Sung Gu; Kang, Noeul; Gulumian, Mary; Bello, Dhimiter; et al. (Frontiers in Toxicology, 2022)
Biomonitoring of workers is an approach of evaluating workers’ exposure to chemicals and particulate matter by measuring biomarkers of parent chemicals, their metabolites, and reaction products in workers’ biospecimens. Prerequisites for biological monitoring in the workplace include permission to enter the workplace, approval of the study plan from the IRB (Institutional Review Board), and obtaining consent from workers. Because of the complex legal process involved in biomonitoring, few studies have been conducted so far on biomonitoring of workers’ exposures to nanoparticles and other hazards from emerging materials and advanced nanotechnologies. We have developed a cell-based biomonitoring device that can evaluate acute cytotoxicity and various other effect biomakers, such as inflammation, at realistic workplace exposure. This device is based on air–liquid interphase (ALI) and can be used to evaluate cell toxicity and early effect biomarkers along adverse outcome pathways. Following exposure of A549 lung epithelial cells in ALI to workplace air for 1–2 h, the cells were processed to assess the induction of inflammatory and cell damage biomarkers. Initially, we estimated the deposition rate of nanoparticles in the transwell by exposing the cell-free ALI device to silver nanoparticle aerosols (AgNP 20–30 nm) for 2 h in the laboratory. Then A549 lung epithelial cells cultured on the transwell in the ALI device were exposed to AgNP nanoaerosols for 2 h and evaluated for cytotoxicity and induction of mRNAs of pro-inflammatory cytokines IL-1b, IL-6, and TNF-α. Then the cells in the ALI device were exposed to 3-D printer emissions at the workplace and evaluated for the same matched endpoints. The mRNA levels for IL-1b, IL-6, and TNF-α increased significantly at the end of 2-h exposure of A549 cells to the positive control AgNP aerosols. These mRNAs, as well as LDH and microprotein concentrations, increased even more after 24-h post-exposure incubation (p < 0.05). Cytotoxicity evaluation of 3-D printer emissions at 810 and 957 μg/m3, which was more than 80 times higher than the airborne total suspended particulate concentrations in the workplace air (9–12.5 μg/m3), suggested no significant acute cytotoxicity at the end of 2-h exposure to 3-D-printing emission, as well as at 24-h post-exposure incubation. Hyperspectral microscopic observation showed that 3-D printers emitted particles to be attached to A549 cells after 2-h exposure, and many particles were internalized by A549 cells after 24 h of post-exposure incubation. The mRNA expression of pro-inflammatory cytokine IL-1b and IL-6 increased significantly after 2-h exposure to 3-D printer emissions and after 24-h incubation (only IL-6). In contrast, the expression of TNF-α mRNA decreased significantly after 2 h of exposure to 3-D printers and decreased even more after 24-h post-exposure incubation. These results support the use of cell-based ALI devices for direct assessment of airborne hazards in the workplace, for probing toxicological properties of airborne contaminants using adverse molecular pathways, and for guiding study design for workplace biomonitoring. ALI devices can bridge conventional exposure assessment with cellular toxicity testing platforms for hazard and risk assessment.